The Influence of People, Process, and Physical Evidence on the Decision to Choose Telecommunication Services - Amri, Fairuza Rikha (CV Raskha Media Group, 2025)
This study aims to analyze the influence of People, Process, and Physical Evidence on consumers’ decisions to choose telecommunication services. In the era of digital communication, the competition among telecommunication companies is increasingly intense, with similar products and pricing structures offered by various providers. Therefore, service quality and the extended marketing mix elements play a crucial role in determining consumer preferences. The research employs a quantitative approach with data collected through questionnaires distributed to users of major telecommunication providers such as Telkomsel, XL, and Indosat. The variables include People (employee competence, friendliness, responsiveness), Process (service procedures, responsiveness, and complaint handling), and Physical Evidence (store design, website appearance, and supporting facilities). The data were analyzed using multiple linear regression to determine both partial and simultaneous effects. The results indicate that the three variables—People, Process, and Physical Evidence—have a positive and significant influence on the decision to choose telecommunication services, either partially or simultaneously. Among them, the Process variable has the most dominant effect, suggesting that efficient and transparent service procedures are key determinants in consumer choice. This study highlights the importance of managing service quality holistically, not only through product and price but also through human interaction, operational efficiency, and tangible service attributes, to enhance competitiveness and customer loyalty in the telecommunication industry.